Probiotics alleviate painful diabetic neuropathy by modulating the microbiota–gut–nerve axis in rats - Ye Jiang; Jing Yang; Min Wei; Jiayin Shou; Shixiong Shen; Zhuoying Yu; Zixian Zhang; Jie Cai; Yanhan Lyu; Dongsheng Yang; Yongzheng Han; Jinpiao Zhu; et al. (Journal of Neuroinflammation)
Abstract Painful diabetic neuropathy (PDN) is one of the most common complications of diabetes. Recent studies suggested that gut microbiota dysbiosis contributes to the development of PDN, but underlying mechanisms remain elusive. In this study, we found decreased probiotics generating bacteria such as Lactobacillus and Bifidobacterium strains in the PDN rats. Supplementation with multiple probiotics for 12 weeks alleviated pain, reversed nerve fiber lesions, and restored neuronal hyperexcitability. Probiotics administration effectively attenuated intestinal barrier impairment, reduced serum lipopolysaccharide and proinflammatory cytokines, and mitigated disruptions in the blood-nerve barrier. Furthermore, probiotics treatment inhibited the activation of the TLR4/MyD88/NF-κB signaling pathway and reduced proinflammatory cytokines in the sciatic nerve of the PDN rats. Together, our findings suggest that gut microbiota dysbiosis participates in PDN pathogenesis, and probiotics offer therapeutic potential via modulating the microbiota-gut-nerve axis. Graphical abstract